2020
DOI: 10.3390/ani10010111
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Computer Records: A Tool to Increase Productivity in Dairy Herds

Abstract: The level of adoption of herd management information system veterinary automated management and production control program (VAMPP) Bovine and its impact on productivity of 912 specialized dairy systems with at least 5 years of information recorded was studied. Herds were classified as low (n = 389), medium (n = 343), or high (n = 180) adoption level on the basis of extent and consistency of record keeping for variables related to production, reproduction, and health. For each herd, within-year averages were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…If material is not included in the article's Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright specific information on dairy cows, such as through the incorporation of on-farm data streams and automated monitoring systems, can improve the thoroughness and effectiveness of data gathering for assessing milk production, reproductive performance, and overall farm management (Celozzi et al 2020). Madouasse et al (2010) and Sánchez et al (2020) added that conducting individual data enables the selection of specific animals within a group and adopting different management techniques. This empowers farmers to make well-informed decisions swiftly, improves their herds' management, and enhances dairy cows' health and production.…”
Section: Challenges and Potential Improvements In The Advancement Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…If material is not included in the article's Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright specific information on dairy cows, such as through the incorporation of on-farm data streams and automated monitoring systems, can improve the thoroughness and effectiveness of data gathering for assessing milk production, reproductive performance, and overall farm management (Celozzi et al 2020). Madouasse et al (2010) and Sánchez et al (2020) added that conducting individual data enables the selection of specific animals within a group and adopting different management techniques. This empowers farmers to make well-informed decisions swiftly, improves their herds' management, and enhances dairy cows' health and production.…”
Section: Challenges and Potential Improvements In The Advancement Of ...mentioning
confidence: 99%
“…Thus, it is important to acknowledge the financial implications of the adoption of dairy recording tools, especially in developing countries. Sánchez et al (2020) explored the expenses associated with providing computer systems, software licences, and other hardware necessary for data gathering and management can be relatively high. Despite this, Koltes et al (2018) agreed that future advancements would necessitate real-time data collection, data management, and the creation of prediction models to facilitate early intervention to prevent or minimize losses in present and future animal populations.…”
Section: Challenges and Potential Improvements In The Advancement Of ...mentioning
confidence: 99%
“…It has been observed in several tropical cattle production systems that record keeping is, at best, inefficient [ 15 ]. For example, González-Padilla et al [ 16 ] observed that 49.1% of Mexican dual-purpose smallholders kept no records, 47.7% had handwritten records, and only 2.8% kept them on a computer.…”
Section: Data Recording and Economical Aspectsmentioning
confidence: 99%
“…Thus, a dichotomy exists between how much the farmer is able to invest in producing more animal products and their economic limitations. Potential solutions to the record dilemma do exist, and tailor-made computer software for record keeping in tropical conditions has become available and has been adopted by livestock farmers in recent years [15,29]. Information storage capabilities have come a long way, along with the education of the farmers, which encourages them to invest time in data entry and analysis (Figure 1).…”
Section: Data Recording and Economical Aspectsmentioning
confidence: 99%